Poly(Methyl Methacrylate) Composites With Modified Human Hair and Their Static and Dynamic Mechanical Properties - Honey Srivastava; Nidhi Nitin Parmekar; S. Pozhil; Sachin Waigaonkar; Rashmi Chauhan (Advances in Polymer Technology)
In this work, the impact of using grafted hair as reinforcing agent for making composites has been studied and compared with composites using virgin hair. For this purpose, the composites have been prepared via compression molding using a thermoplastic resin, poly(methyl methacrylate) (PMMA), as matrix, and virgin or grafted human hair (HH), HHact-g-PMMA_1.75, and HHact-g-PMMA_2, with 56% and 78% of grafting percentages, respectively, were taken as reinforcement material, and their properties have been compared. The hair weight fractions in composites were varied from 15% to 60%. The SEM micrographs of the fractured surface of the tensile specimen of virgin HH-reinforced PMMA composites show hair pullouts. In contrast, in graft copolymer-reinforced PMMA composites, failure mainly occurs at the hair and not at the hair–matrix interface, showing better adhesion. This was supported by AFM images in which a decrease in surface roughness for grafted hair-reinforced composites was observed. The PMMA composites with grafted hairs showed improved mechanical properties than PMMA in contrast to composites with virgin hairs in which there was loss of tensile strength. On addition of 15% of HHact-g-PMMA_1.75, the tensile strength raised by 21.86%, while in the case of HHact-g-PMMA_2 graft copolymer, the tensile strength was increased by 87.44% w.r.t virgin HH. The hair content up to 45% showed improvement in mechanical properties; however, further increase in hair content leads to a decrease in the mechanical strength. Dynamic analysis also showed an increase in storage (E′) and loss modulus (E′′), enhanced with the increase in hair concentration and reached the maximum for the 55:45::PMMA:hair ratio. The increase in E′ and E′′ was more when grafted hairs were used as the reinforcing agents. As compared to composites with virgin HH, an increase of 57–98% for E′ and 46–80% for E′′ was observed for composites with HHact-g-PMMA_1.75. Similarly, for HHact-g-PMMA_2 hairs, an increase of 49–102% in E′ and 45–98% for E′′ was observed. The present work thus shows that the use of grafted hairs results in the enhancement of adhesion of hair and matrix resulting in the improved properties.